2016
DOI: 10.1016/j.semcancer.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the molecular targets of dietary flavonoid fisetin in cancer

Abstract: The last few decades have seen a resurgence of interest among the scientific community in exploring the efficacy of natural compounds against various human cancers. Compounds of plant origin belonging to different groups such as alkaloids, flavonoids and polyphenols evaluated for their cancer preventive effects have yielded promising data, thereby offering a potential therapeutic alternative against this deadly disease. The flavonol fisetin (3,3′,4′,7-tetrahydroxyflavone), present in fruits and vegetables such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 90 publications
1
38
0
Order By: Relevance
“…These activities are regulated by many factors such as the BCL-2 family, Bax and PARP. It is well-known that fisetin interacts with many different signaling cascades to regulate critical cellular processes (24,36). Fisetin has been reported to induce cell-cycle arrest (37), induce apoptosis via inhibiting anti-apoptotic proteins, and impair phosphorylation of MEK and AKT in various cancer cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…These activities are regulated by many factors such as the BCL-2 family, Bax and PARP. It is well-known that fisetin interacts with many different signaling cascades to regulate critical cellular processes (24,36). Fisetin has been reported to induce cell-cycle arrest (37), induce apoptosis via inhibiting anti-apoptotic proteins, and impair phosphorylation of MEK and AKT in various cancer cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…(tomatoes, onions, and cucumbers), nuts, and wine 12,13 . Fis has attracted attention for its multi-functional therapeutic activities that include anti-cancer 14 , anti-diabetic 15 , and neuroprotective 16 effects in cell culture and in animal models relevant to human diseases. Fis has a remarkable spectroscopic attribute of an exquisitely sensitive intrinsic 'two colour' fluorescence, which arises due to a photoinduced excited state intramolecular proton transfer (ESIPT) reaction (Scheme 1) 17,18 .…”
mentioning
confidence: 99%
“…Fisetin is a natural product, which is readily available. Fisetin is a potent antioxidant and is thought to exert its antioxidant effect by activating heme oxygenase-I (HO-I) under oxidative stress conditions 22 . It has also been shown that fisetin suppresses NFκB signaling pathway and MAPKs.…”
Section: Discussionmentioning
confidence: 99%